Attainability analysis in the problem of stochastic equilibria synthesis for nonlinear discrete systems - Bashkirtseva, Irina; Ryashko, Lev (Zielona Góra: Uniwersytet Zielonogórski)
A nonlinear discrete-time control system forced by stochastic disturbances is considered. We study the problem of synthesis of the regulator which stabilizes an equilibrium of the deterministic system and provides required scattering of random states near this equilibrium for the corresponding stochastic system.
Keywords: stochastic sensitivity function; attainability; chaos suppression